With a Small ‘f’: An Exploration of the Therapist’s Experience and Understanding of Faith. A Hermeneutic Literature Review - Russell, Charriere Louise (Auckland University of Technology, 2022)
Small ‘f’ faith is a crucial yet intangible aspect of psychotherapeutic praxis, which may invisibly complement and contribute to the common healing factors of psychotherapy, alongside hope. However, bringing faith into the open is challenged by the task of communicating its numinous qualities in words and the ever-present conflation of small ‘f’ faith with its religious guise. This research asks, “What is the trainee psychotherapist’s understanding and experience of small ‘f’ faith?” A hermeneutic interpretative approach uses the philosophical ideas of Gadamer (2013) and Heidegger (1996) guide and frame how the psychotherapy literature was reviewed, where fore-understandings shape and guide the interpretation of the literature to provide a unique understanding of the topic. Aspects of Romanyshyn’s alchemical hermeneutics also invite the researcher’s unconscious engagement in the process of asking questions of the literature. The review reveals how small ‘f’ faith has been overshadowed by a focus on big ‘F’ Faith, understood as theological thought and religious practice. The findings offer a meaningful understanding of small ‘f’ faith as being innate and numinous, conveying qualities of openness and steadfastness, and being abiding and facilitative. How faith underpins psychotherapeutic work with clients—and could underpin the development of trust and hope—highlights the need for psychotherapy training to creatively engage with small ‘f’ faith.